Plantation Regulation In The Palm Industry Sector In The Omnibus Law Of Employment Creation (Cipta Kerja) - Sugiyono, Heru; Haryanto, Imam (Faculty of Law, Pembangunan Nasional Veteran Jakarta University, 2021)
The ratification of Law Number 11 of 2020 concerning Employment Creation (Omnibus Law Employment Creation) massively amends, deletes, or sets new rules against several previous laws, such as Law Number 39 of 2014 concerning Plantations (Plantation Law) and other regulations. Some of the contradictions that have arisen between the Plantation Law and the Omnibus Law Employment Creation, of course, have an influence on the palm oil industry sector in Indonesia, causing legal uncertainty. The problem raised in this study is about how the plantation regulation in the palm oil industry sector is in the Omnibus Law Employment Creation. The research objective is to analyze the legal certainty of plantation regulations in the palm oil industry sector in the Omnibus Law Employment Creation. The research method used is juridical normative, that is, research is carried out through literature study with secondary data. The results show that the plantation regulations in the palm oil industry sector in the Omnibus Law Employment Creation contain legal uncertainty, where in the Omnibus Law Employment Creation there are several contradictions with the provisions of the previous Plantation Law, such as the culture of prioritizing foreign investors, and not in accordance with protection and management of environment. It is necessary to review laws and regulations, especially for the sustainability of the palm oil industry sector, by harmonizing all the rules contained in the Omnibus Law Employment Creation.